Knowledge Management in Libraries and Information Centers: A Bibliometric Perspective - Jain, Priti (Advances in Social Sciences Research Journal, 2020)
The purpose of this paper is to provide a bibliometric perspective of Knowledge Management (KM) literature in libraries for the past 21 years (1998-2019), based on Web of Science core collection bibliographical database. The objectives of the paper are to examine a bibliometric profile of publications in the field of KM in libraries and analyze the emerging research trends in KM research in libraries and information centers through Keyword co-occurrence. This study used bibliometric and citation analysis methods to explore the profile and research trends in knowledge management research in libraries. A total of 83 sources were retrieved via Web of Science’s core collection database using the terms “Knowledge Management, Libraries, Information centers, librarians, information professionals”. Data was analyzed through Web of Science’s Clarivate Analytics, then exported to Microsoft Excel and VOSviewer for production of images and graphs. Findings revealed that the most research outputs were produced in year 2018 mostly in article forms and the University of South Africa led in contribution to knowledge management research in libraries. Findings also determined top 10 prolific authors and publishing sources; most research were produced by United States, followed by South Africa. As most KM research is carried out on perceptions, predictions and benefits of KM in libraries and information centers not on KM practice in libraries and its impact on the quality of library services. This has implication on KM practice in libraries and information centers. Practicing librarians are unable to apply KM emulating success stories and best practices of libraries and information centers. Bibliometric studies on KM are too general, and to the best knowledge of the researcher, none of them so far gives a clear view of research trends of KM in libraries. Hence, this might be the first study to fill this gap, which only analyzed a sample of documents which are more relevant to the scope of the study.